The game theory: Malaysia’s position in south China sea towards China’s string of pearls strategy - Lau, Cheng Yong; Ang, Wen Loong (American Scientific Publishers, 2016)
This article investigates the on-going issue that is associated with China’s String of Pearls (SOP) strategy in South China Sea which has trespassed on Malaysia’s water territories, analyzed from the perspectives of military costs, international business trade relation, and natural resources acquisition as well as its possible impact on Malaysia’s position in South China Sea using the game theory. China’s vision is to expand its seaborne trading route strategy to secure its commodity and energy transaction by mobilizing the sea channel ’silk road’, otherwise also known as the String of Pearls strategy. Each ‘pearl’ plays a unique, different role in different location for its mixed strategy in the international trading area especially in the Spratly Islands. Currently, China has been aggressive in the South China Sea by provoking Vietnam, the Philippines, and Malaysia. Therefore, international trade relation between China and Malaysia is questionable. However, Malaysia’s ‘status quo’ strategy that is analyzed and reflected in the game theory may be adopted as the possible solution to this pertinent issue, paving the way for Malaysia to also serve as a role model within the ASEAN region to end the conflict and gain sustainable economic growth.